Buku panduan 41 taman nasional di Indonesia: Guidebook of 41 national parks in Indonesia (Ministry of Forestry, UNESCO and CIFOR, 2003)
This guidebook introduces the 41 national parks in Indonesia, with maps describing the biodiversity, unique features and characteristics of these national parks, and where they can be found. For natural travels, it tells about the main attractions and the significant values that people must care about. This diversity and the unique characteristics of endemic, endangered and protected flora and fauna as well as the wonders of natural phenomena and landscapes, can perhaps best be witnessed in this country's national parks. As of March 2003, 41 national parks have been designated, with total areas 14,973 hectares that covers terrestrial and marine of national parks.